Review on Queueing Problem in Healthcare - Ariff, Hajar; Kamardan, M Ghazali; Sufahani, Suliadi; Ali, Maselan (International Journal of Engineering and Technology, 2018)
This article shows the application of queueing, simulation and scheduling used in the field of healthcare. A summary of queueing, simulation and scheduling theory used in waiting time, appointment system and patient flow are summarised in this article. Different departments in the healthcare system are also considered in this article such as emergency department, outpatient department and the pharmacy. The aim is to provide the reader a general background into queueing, simulation and scheduling in the healthcare.